Raising awareness on physician-patient communication in IPF: an Italian multicenter study exploring the pulmonologist’s perspective: Physician-patient communication in IPF - Tomassetti, Sara; Sebastiani, Alfredo; Caminati, Antonella; Oggionni, Tiberio; Davì , Michele; Ghirardini, Alessandra; Martinoli, Monica M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background: Idiopathic pulmonary fibrosis (IPF) remains a debilitating, poor prognosis disease requiring a patient-centered approach. Objectives: To explore the pulmonologist’s perspective on physician-patient communication. Methods: A faculty of psychologists and pulmonologists organized a training course consisting of two workshops 12 months apart. Self-assessment questionnaires (pre- and post-course), role play (RP) simulations (during both workshops) and clinical consultation observations followed by semi-structured interviews (in the 12-month period) were employed to evaluate the pulmonologists’ knowledge of patient-centered medicine and communication/relational skills, their communication style and possible communication/relational difficulties. Results: Twenty-three pulmonologists attended the first workshop, 14 the second one and 10 both. They were interested in patient-centered medicine and communication but felt the need for deeper knowledge and improved skills; during the first workshop, a more disease-oriented approach emerged. However, the training yielded some improvements, like more frequent patient agenda exploration. The patients’ poor knowledge of IPF was among the barriers hampering effective communication. Conclusions: Despite the overall disease-prone approach to IPF patients, there was room for improvement through adequate training. In practice, adequate training may ameliorate communication and drive towards patient-centeredness. Raising awareness on these topics is crucial to ensure IPF patients optimal care. The pulmonologists’ needs may help planning interventions.